SPECIFICATION OF ACCOUNTING OF FIXED ASSETS UNDER INTERNATIONAL AND RUSSIAN STANDARDS - T. Rogulenko; E. Egorova (Вестник университета, 2017)
The problems of definition and recognition of fixed assets are considered. The current Accounting Regulation «Accounting for Fixed Assets» is compared with the International Standard «Fixed Assets» in terms of determining and recognizing objects in accounting and reporting.